Pengembangan E-Modul Multimedia Interaktif Berbasis Platform Pemrograman Visual Pada Materi Berpikir Komputasional Untuk Meningkatkan Capaian Pembelajaran Kognitif Informatika Siswa SMP - Ade Lia Al Rahmah; Ade Novi Nurul Ihsani; Nur Qudus; Sri Endah Wahyuningsih (Universitas Pakuan, 2026)
DEVELOPMENT OF INTERACTIVE MULTIMEDIA E-MODULES BASED ON VISUAL PROGRAMMING PLATFORMS ON COMPUTATIONAL THINKING MATERIALS TO IMPROVE COGNITIVE INFORMATICS LEARNING ACHIEVEMENTS OF JUNIOR HIGH SCHOOL STUDENTS This research is motivated by the low computational thinking skills and cognitive learning outcomes of junior high school students in Informatics, caused by conventional learning methods and limited laboratory facilities. This study aims to develop, test the feasibility, practicality, and effectiveness of an interactive multimedia E-Module based on a visual programming platform (Scratch) for Computational Thinking materials. The research method employed is Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects involved ninth-grade students involved at SMP Negeri 2 Toroh, divided into experimental and control classes. Data collection was carried out through expert validation questionnaires, user response questionnaires, and learning outcomes tests (pretest and posttest). The results showed that the E-Module developed using Articulate Storyline was declared highly feasible based on material and media expert validations. This product was also rated as highly practical based on positive responses from teachers and students. The effectiveness test using the Mann-Whitney test revealed that the Mean Rank of the experimental class (37.85) was significantly higher than the control class (26.33), along with an increased N-Gain score. It is concluded that this interactive multimedia E-Module is effective in improving the cognitive learning outcomes of junior high school Informatics students.